P495 Is narcolepsy incidence increasing or symptoms just better recognised?. (June 2019) - Hayden, Jennifer; Dann, Lisa; Allen, Nicolas M; Lynch, Bryan
Abstract : Background: Narcolepsy is a rare and under-recognised disease characterised by excessive daytime sleepiness, disturbed nocturnal sleep, hallucinations, and cataplexy, with a major impact on quality of life. Diagnosis can be challenging. We present a series of recent children presenting to a district general hospital over a 2.5 year period with chronic symptoms ultimately diagnosed with narcolepsy. Patients: Patient 1: Female(12y) GP referral with 2-year history of increased sleepiness and falling asleep during meals. Later developed cataplexy-'when I laugh, I go weak suddenly'. Swine-flu vaccine 6 years previously. Patient 2: Female(8y) GP referral with 18-month history of excessive day-time sleepiness and vivid nightmares. Narcolepsy was considered when seen in clinic initially but significant academic decline subsequently prompted formal diagnosis (9 months after referral). Laugh induced catatonia (eyes roll, tongue protrusion and lower limb weakness). Pandemrix H1N1 vaccine 3 years previously. Sleep study noted abnormal sleep latency and sleep onset REM periods. Improvement with methylphenidate. Patient 3: Male(10y) emergency department (ED) presentation with a 2-month history of excessive day time sleepiness and increased appetite. Falling asleep while standing occasionally. No cataplexy. Sleep study abnormal (2.3 minutes sleep latency and SOREM periods in 3/4 naps). Treatment with sodium oxybate. Patient 4: Female(5y) ED presentation with 2-month history of daily episodes of eye rolling and sudden collapse, weeks following MMR. Initial diagnosis and treatment for epilepsy. Video review reveals clinical diagnosis of cataplexy; focused history revealed excessive daytime sleepiness. Treatment with stimulants (methylphenidate) improved sleep symptoms; considering sodium-oxybate for cataplexy. Patient 5: Male(15y) GP referral with 3 year history of excessive day-time sleepiness, struggling to keep up academically. Upon laughing his mouth droops open with tongue protrusion (cataplexy). No swine-flu vaccine. Treatment pending investigations. Patients 1–4 had undetectable CSF hypocretin levels (except patient 2; failed LP) and positivity for the HLA-DQB1*0602 association in keeping with narcolepsy. Patient 5 is awaiting specific investigations. Sleep studies are pending for 3 patients. Secondary causes of narcolepsy were out-ruled. Discussion: Delay in narcolepsy diagnosis is associated with worse outcomes. While narcolepsy is thought to be under recognised, these 5 patients were suspected upon referral to paediatrics and management instigated quickly; however focused history and increased awareness is required. Our series and review of a national narcolepsy clinic suggests increased incidence and early detection in children. A national narcolepsy service (currently Temple-St-Hospital, Dublin) facilitates management, as symptoms and co-morbidities can be debilitating and life-long. Vaccine association remains controversial.